2021
DOI: 10.1111/jocs.15989
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter closure for postinfarction ventricular septal defect: A meta‐analysis of the current evidence

Abstract: Objective: Postinfarction ventricular septal defect (PIVSD) is a severe complication of acute myocardial infarction (AMI). Transcatheter closure (TCC) is an alternative option to surgical repair. This study was undertaken to examine the published literature to provide objective evidence for TCC using a meta-analysis. Methods:We searched for significant medical and publisher databases. Two reviewers checked the quality of the studies and extracted data. Eligible studies included single-arm studies and comparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Moreover, it has been recently demonstrated that transcatheter device closure of perimembranous VSD and intracristal VSD can be performed safely and successfully in selected patients with excellent medium- and long-term results [ 88 ]. Interestingly, repair of post-MI septal rupture with transcatheter defect closure emerges as a viable option [ 89 ].…”
Section: Treatment Modalities Targeting Diseases Of the Ivsmentioning
confidence: 99%
“…Moreover, it has been recently demonstrated that transcatheter device closure of perimembranous VSD and intracristal VSD can be performed safely and successfully in selected patients with excellent medium- and long-term results [ 88 ]. Interestingly, repair of post-MI septal rupture with transcatheter defect closure emerges as a viable option [ 89 ].…”
Section: Treatment Modalities Targeting Diseases Of the Ivsmentioning
confidence: 99%
“…Transcatheter closure of post-infarct VSD could be an encouraging alternative treatment method that is less invasive and advocated by national guidelines [5]. Although an absence of firm tissue to seat the device for significant defects may be problematic [6]. Post-infarct VSD is usually diverse in shape, which may change throughout the cardiac cycle and could be accompanied by septal rupture [7], which led in the present case to the decision of surgical intervention.…”
Section: Discussionmentioning
confidence: 98%
“…A repeat transesophageal echocardiography demonstrated no residual shunt. Izabela Warchoł et al, A case study of post-myocardial infarction ventricular septal defect of advanced age and surgical expertise that is not easily accessible [6].…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatment was adopted in a few patients (mostly LVFWR), with a mortality exceeding 90%, confirming previous data [ 13 ]. On the other hand, percutaneous treatment was adopted most often in VSR patients, showing that alternative therapeutic strategies are progressively finding their space for selected patients, although results were slightly suboptimal, if compared to surgery [ 29 ].…”
Section: Discussionmentioning
confidence: 99%